Genomic insights into familial adenomatous polyposis: unraveling a rare case with whole APC gene deletion and intellectual disability - Hiroki Tanabe; Masami Ijiri; Kenji Takahashi; Honoka Sasagawa; Tomomi Kamanaka; Shohei Kuroda; Hiroki Sato; Takeo Sarashina; Yusuke Mizukami; Yoshio Makita; Toshikatsu Okumura (Human Genome Variation)
Abstract A young patient diagnosed with advanced colon cancer and liver metastasis was found to have familial adenomatous polyposis (FAP) through comprehensive genomic analysis. Whole-genome array comparative genomic hybridization (aCGH) revealed germline deletions at chromosome 5q22.1-22.2 encompassing the entire APC gene. The patient and her son exhibited mild intellectual disability without developmental delay. This case highlights the need for further exploration of the characteristics associated with whole APC deletions. aCGH is a valuable tool for studying FAP and provides a detailed analysis of large deletions.